A Comprehensive Review of Nursing Education and Training in Iraq: Current Status and Future Directions - Ahmed, Sirwan; Omar, Rukhsar Muhammad; Abdulqadir, Salar Omer (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2024)
The landscape of nursing education in Iraq is deeply shaped by historical, political, and social factors. Originating in the early 20th century, Iraqi nursing education has evolved to meet healthcare demands, yet faces obstacles such as resource limitations, faculty shortages, outdated curricula, and regulatory gaps. To ensure its future, comprehensive reforms are imperative. Collaboration with foreign institutions for curriculum standardization is crucial, aligning with global excellence standards. Addressing faculty shortages requires substantial investments in mentorship programs and incentives to nurture a proficient faculty. Partnerships with healthcare facilities are vital for enhanced clinical training, promoting interprofessional teamwork and preparing students for diverse healthcare settings. The future of nursing education in Iraq relies on adaptation, innovation, and alignment with global benchmarks to foster a skilled nursing workforce. This study proposes transformative paths to elevate nursing education, aiming to enhance healthcare quality and the nation's well-being.